STAFF EMPOWERMENT IN BPJS DEPARTMENT ON THE STRATEGY TO INCREASE PATIENT SATISFACTION BPJS IN GRANDMED LUBUK PAKAM HOSPITAL - Reni Aprinawaty Sirait (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
BPJS Health is a legal entity formed to administer the health insurance program. Health insurance is a guarantee in the form of health protection so that participants get health care benefits and protection in meeting basic health needs that are given to everyone who has paid or whose contributions are paid by the government. This activity aims to provide health education about empowering staff in the BPJS section on strategies to increase BPJS patient satisfaction. The method of implementing the activity is using observation sheets and questionnaires about empowering staff in the BPJS. From the results of the activities carried out by the staff at the BPJS, they were very enthusiastic about welcoming this activity. Through this activity, it is hoped that the staff in the BPJS section can be more active in providing health services, especially to BPJS patients, so as to increase BPJS patient satisfaction. Through this activity, it is also beneficial for BPJS patients, which can be handled quickly to get health services at the BPJS section. BPJS patient satisfaction can be measured by increasing return visits for treatment to the BPJS section, patient satisfaction is measured by health service aspects such as: tangible, reliability, responsiveness, assurance and empathy. The implementation of community service in empowering staff in the BPJS to increase BPJS patient satisfaction is carried out with the enthusiasm of the audience. The role of staff in the form of tangible, reliability, responsiveness, assurance and empathy is an important factor in increasing BPJS patient satisfaction. The main thing to create patient satisfaction is truly quality health services. If the health services perceived by the patient are of good quality and provide a healing effect, of course it will affect the satisfaction of each patient. The quality of a health service according to the results of this study, the health service is able to realize patient satisfaction.